2011
DOI: 10.1084/jem.20110578
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Roquin induces early death and immune deregulation but not autoimmunity

Abstract: Deletion of Roquin in T or B cells, or in the entire hematopoietic system of mice, alters immune homeostasis but does not result in autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 19 publications
5
117
1
Order By: Relevance
“…Loss of Roquin, either specifically on T cells or in the hematopoietic system, caused expansion on CD8 + effector-like T cells but not autoimmunity (28). In contrast, Roquin bearing the san allele, which is a gain-of-function-allele (29, data not shown), causes follicular helper T (Tfh) cell-dependent lupus (30)(31)(32)(33); it is achieved, at least in part, through posttranscriptional regulation of Icos mRNA.…”
Section: Cd8 + T Cells Responding To Viral Infections Initiate Their mentioning
confidence: 96%
“…Loss of Roquin, either specifically on T cells or in the hematopoietic system, caused expansion on CD8 + effector-like T cells but not autoimmunity (28). In contrast, Roquin bearing the san allele, which is a gain-of-function-allele (29, data not shown), causes follicular helper T (Tfh) cell-dependent lupus (30)(31)(32)(33); it is achieved, at least in part, through posttranscriptional regulation of Icos mRNA.…”
Section: Cd8 + T Cells Responding To Viral Infections Initiate Their mentioning
confidence: 96%
“…33,34 In addition, a recent study showed that the loss of roquin induced early death and immune dysregulation but not autoimmunity in sanroque mice. 35 Therefore, future studies are required to completely elucidate the mechanisms behind pathogenesis of lupus in sanroque mice. T H -cell differentiation is polarized toward T FH cells to generate B-cell responses against infections.…”
Section: T Fh Cells In Murine Models Of Autoimmune Diseasesmentioning
confidence: 99%
“…Germ-line Roquin-deficient mice are perinatally lethal, so tissue-specific ablation of Roquin in T cells, B cells, and hematopoietic cells does not cause autoimmunity (24). For gain of function via Roquin overexpression, we established Roquin Tg mice.…”
Section: Discussionmentioning
confidence: 99%